Online medical consultation: a review - Singh, Ajeet Pal; Joshi, Hari Shanker; Singh, Arun; Agarwal, Medhavi; Kaur, Palveen (International Journal Of Community Medicine And Public Health, 2018)
The Internet has been a steady source of medical data previously; it has just as of late been utilized for online private patient-doctor consultations. As of late, the market has seen a surge in applications providing healthcare services on the go. An online consultation has secured a foothold in the market and individuals are opening up to the likelihood of substituting a visit to a physical facility with an online option. This study reports a review of the literature on online medical consultation from various databases as well as various surveys and reports published. As per published work/reports/surveys, the various factors which led to a sudden surge in the online medical consultation are the convenience, shift in disease patterns, cost-effective, privacy and second opinion.